CLOTHES SALES ADVERTISEMENT AT MARKET PLACE ON THE INTERNET (APPRAISAL STUDY IN SYSTEMIC FUNCTIONAL LINGUISTICS) - NETTY NURDIYANI (International Journal of Innovations in Engineering Research and Technology, 2021)
Wide use of the internet in the Era of The Industrial Revoluiton 4.0 has provided chances for everybody to conduct a sale transaction in the internet. One can make an advertisement to promote his/her products or services. A product or service promoting advertisement will affect readers or buyer candidates to slect the advertised products or services. To find out such persuasive forms, an Appraisal System within the Systemic Functional Linguistics is used. This article was written to describe the three subcategories under the Attitude Domain, namely Affect, Judgment, and Appreciation. Data for the article were collected from the clothes sale advertisements at the Market Place on the Internet in December 2018. A purposive sampling was adopted to collect the data. Data analyses were implemented using the steps suggested by Spradely which included domain, taxonomic, component analysis, and cultural values. Results of the analyses showed that those three subcategories of Attitude, namely Affect, Judgment, and Appreciation were used by writers of the advertisements to promote their clothe products. The most common used Affect was the Security Affect: Confidence. Under the Judgment subcategory, the writers gave more negative Affect to the readers and gave positive Affect to themselves as a party having competence, honesty, and ethics. In their advertisements, the writers gave positive Appreciation to the promoted products. Positive evaluation contained in the Affect, Judgment and Appreciation comprised one attitude that the advertisement writers should possess. Such writers would be brave to expose and describe their products and judge themselves that they possess good attitude, competence and honesty.